THE EFFECT OF THE TALKING STICK LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS IV STUDENTS IN THE SUBJECT OF MATHEMATICS MIXED ACCOUNTING OPERATIONS - Firdausi, Farihah; Nuriadin, Ishaq (Universitas Pakuan, 2024)
The aim of this research is to determine the effect of the Talking Stick learning model on learning outcomes for fourth-grade elementary school students. This research method uses a quantitative method with a quasi-experimental approach and a non-probability sampling technique. Researchers used pre-tests and post-tests to determine the development and impact of students' learning results by implementing the Talking Stick learning model. The data collection technique in this research uses hypothesis testing (t-test) to determine the effect of the talk stick collaborative learning model on critical mathematical thinking. This is reflected in the results of the hypothesis test (t-test) which has a significance value of 0.006 0.05. Therefore, it can be concluded that there is an influence on the learning outcomes of mixed arithmetic operations using the Talking Stick learning model.